Quantıtatıve Evaluation of Knee Radiographies in Patients wıth Osteoarthritis - Şahin, Sezai; Kamanlı, Ayhan (Fırat University, 2001)
Certain practical parameters are needed for progres1s measurements in osteoarthritis (OA) patients. In the present study, joint spaces were measured on the knee radiographs of 21 OA patients and 20 healthy subjects, which were taken both in stand up and supine positions, and were compared. Bilateral joint spaces of the OA patients were found narrowed when compared with the control group. In addition, the comparison among each group showed that bilateral tibiofemoral joint spaces on the radiographs taken in stand up position were narrower than the radiographs taken in supine position, and narrowing in medial joint space is greater (p

Osteoartritli (OA) hastalarda süreç ölçümleri için pratik bazı parametrelere ihtiyaç duyulmaktadır. Bu çalışmada 21 OA'lı hasta ile 20 sağlıklı bireyin ayakta ve yatarak çekilen diz radyografilerinde eklem aralıkları kantitatif olarak karşılaştırıldı. OA'lı hasta grubunda bilateral medial eklem aralıkları kontrollere göre daha dar bulundu. Ayrıca her grup kendi aralarında karşılaştırıldığında ayaktaki grafilerde, yatarak çekilenlere göre bilateral tibiofemoral eklem aralıklarının daha dar olduğu, medial eklem aralığının daha çok daralma gösterdiği (p
OSTEOARTRİTLİ HASTALARDA DİZ GRAFİLERİNİN KANTİTATİF DEĞERLENDİRİLMESİ